Tantangan Pembelajaran Bahasa Inggris Pada Aspek Berbicara Pada Sekolah Pariwisata Dalam Masa Pandemi - Kadek Wiramarta (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
During Covid-19 pandemic, online learning has been the only option to continue learning process. For tourism vocational school, in learning English for Foreign Language, especially in the speaking aspect, the learning process can be a challenge. This research is a qualitative research which aims to see the teacher's perspective regarding challenges of speaking learning process in EFL context. Six educators were interviewed to answer this question. Based on the results of interviews, it was obtained that teachers experienced various challenges during learning process which included technical difficulties, challenges during the learning process and challenges in assessment. Through this research, it is hoped that further strategies to solve these challenges can be formulated.Keyword : challenge, english for foreign language, online learning, speaking.